Serum levels of free heat shock protein 70 and anti-HSP70 are elevated in Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2008)
Objectives. As heat shock proteins (HSPs) are described as candidate self-antigens in Behcets disease (BD), free HSP70 and anti-HSP70 levels were measured in the sera of patients to investigate their role in the pathogenesis of BD. Methods. Free human HSP70 levels were measured ill the sera of patients with BD and compared to disease controls [patients with rheumatoid arthritis (RA) or recurrent oral ulcerations (ROU)] and health-v controls (HC) using ELISA. Anti-HSP70 antibody levels were also determined. Results. Free human HSP70 levels were significantly elevated ill BD sera (1.12 +/- 0.86 ng/ml) compared to HC (0.67 +/- 0.46 ng/ml, BD vs. HC; p<0.001). However similarly elevated levels were also presented in ROU (0.95 +/- 1.01 ng/ml, p<0.05) and RA (1.1 +/- 23.3 ng/ml, p<0.01). Anti-HSP70 antibody levels were also significantly higher in BD (668 +/- 658 mu g/ml) compared to HC (490 +/- 742.05 mu g/ml, p<0.05). However no significant anti-HSP70 antibody responses were observed in ROU (634.7 +/- 548.21 mu g/ml) and RA (431.8 +/- 840.98 mu g/ml). No association of any organ manifestation, the disease duration, or treatment with HSP70 or anti-HSP70 antibody levels were observed in BD. A correlation between HSP70 and anti-HSP70 levels was only found in HC (p=0.007). Conclusions. Free human HSP70 and anti-HSP70 antibodies are both elevated in patients with BD. HSP70-mediated innate and adaptive immune responses may participate in proinflammatory cytokine activation and tissue destruction in BD.
Keywords: Behcet's disease; Heat shock protein 70; ANTIGEN-PRESENTING CELLS; HEAT-SHOCK-PROTEIN; EXTRACELLULAR HSP70; IMMUNE-RESPONSES; ANTIBODIES; PEPTIDES